Cooperative Magnetism in Crystalline N‐Aryl‐Substituted Verdazyl Radicals: First‐Principles Predictions and Experimental Results. Issue 25 (18th April 2017) - Eusterwiemann, Steffen; Dresselhaus, Thomas; Doerenkamp, Carsten; Janka, Oliver; Niehaus, Oliver; Massolle, Anja; Daniliuc, Constantin G.; Eckert, Hellmut; Pöttgen, Rainer; Neugebauer, Johannes; Studer, Armido
Abstract: We report on a series of eight diaryl‐6‐oxo‐verdazyl radicals containing a tert ‐butyl group at the C(3) position with regard to their crystal structure and magnetic properties by means of magnetic susceptibility measurements in combination with quantum chemical calculations using a first‐principles bottom‐up approach. The latter method allows for a qualitative prediction and detailed analysis of the correlation between the solid‐state architecture and magnetic properties. Although the perturbation in the molecular structure by varying the substituent on the N ‐aryl ring may appear small, the effects upon the structural parameters controlling intermolecular magnetic coupling interactions are strong, resulting in a wide spectrum of cooperative magnetic behavior. The non‐substituted 1, 5‐diphenyl‐ tert ‐butyl‐6‐oxo‐verdazyl radical features a ferromagnetic one‐dimensional spin ladder type magnetic network—an extremely rarely observed phenomenon for verdazyl radicals. By varying substituents at the phenyl group, different non‐isostructural compounds were obtained with widely different magnetic motifs ranging from linear and zigzag one‐dimensional chains to potentially two‐dimensional networks, from which we predict magnetic susceptibility data that are in qualitative agreement with experiments and reveal a large sensitivity to packing effects of the molecules. The present study advances the fundamental understanding between solid‐state structure and magnetism in organically based radical systems. Abstract : Cooperative magnetic effects : The preparation of a series of eight tert ‐butyl‐substituted 1, 5‐diaryl‐6‐oxo verdazyl radicals and the characterization of the magnetic susceptibilities are presented. Quantum chemical calculations revealed different complex magnetic networks including ferromagnetic and antiferromagnetic one‐ and two‐dimensional networks. This study highlights the relationship between crystal structure and magnetic properties.